Job satisfaction and value creation: antidotes for business educators’ job retention - Owenvbiugie Robinson Osarumwense, (Technium Social Sciences Journal, 2020)
The study assessed how job satisfaction and value creation serve as antidotes to job retention of employees in higher institutions in Edo and Delta States. Variables such as tenure, salary, excellent compensation and training and development were assessed. Four research queries were provided answers to. Two reasonable guesses were tested. Survey research was applied. 189 business educators were used for the study. A total of 179 questionnaires were found usable representing 94.7 percent. The instrument was validated by Three experts validated the items in the questionnaire. The instrument yielded 0.98 using the Cronbach alpha to enhance its face and content validity. The descriptive statistics was used to answer all questions raised for the study. The reasonable guesses were tested with the t-test statistics. Lecturers’ Job Satisfaction and Value Creation Questionnaire (LJSVCQ) were administered on the respondents by the researcher with two supporting persons. Results revealed business educators: male and female, married and single, were satisfied with job tenure, salary they earned. It also revealed business educators were satisfied with excellent compensation, training and development. Male do not differ with female business educators in their levels of job satisfaction. Married lecturers do not differ from single business educators in their levels of job satisfaction. The study recommended that business educators’ job satisfaction may be improved if management and councils of various tertiary institutions pay necessary attention to staff welfare in terms of regular review of salary paid to staff, and security of workers’ job.